Preparation and reactivity of rhodium and iridium complexes containing a methylborohydride based unit supported by two 7-azaindolyl heterocycles - Da Costa, Rosenildo Correa; Rawe, Benjamin W.; Tsoureas, Nikolaos; Haddow, Mairi F.; Sparkes, Hazel A.; Tizzard, Graham J.; Coles, Simon J.; Owen, Gareth R. (Dalton Transactions, 2018)
The synthesis and characterisation of a new anionic flexible scorpionate ligand, methyl(bis-7-azaindolyl)borohydride [MeBai]- is reported herein. The ligand was coordinated to a series of group nine transition metal centres forming the complexes, [Ir(MeBai)(COD)] (1), [Rh(MeBai)(COD)] (2), [Rh(MeBai)(CODMe)] (2-Me) and [Rh(MeBai)(NBD)] (3), where COD = 1,5-cyclooctadiene, CODMe = 3-methyl-1,5-cyclooctadiene and NBD = 2,5-norbornadiene. In all cases, the boron based ligand was found to bind to the metal centres via a κ3-N,N,H coordination mode. The ligand and complexes were fully characterised by spectroscopic and analytical methods. The structures of the ligand and three of the complexes were confirmed by X-ray crystallography. The potential for migration of the "hydride" or "methyl" units from boron to the metal centre was also explored. During these studies an unusual transformation, involving the oxidation of the rhodium centre, was observed in complex 2. In this case, the η4-COD unit transformed into a η1,η3-C8H12 unit where the ring was bound via one sigma bond and one allyl unit. This is the first time such a transformation has been observed at a rhodium centre.